Odsevi politične filozofije v pravu socialne varnosti - Mišič, Luka (Delavci in delodajalci, 2018)
In the contribution, I explore the reflections of three theories of political philosophy in social security law, i.e. in the domestic social insurance and social assistance scheme and also, to a lesser extent, at the level of the European Union. The theories I have selected for this undertaking are liberalism, libertarianism and communitarianism. Each one of them is namely permeated by values that can make an important contribution to the regulation of social security and determine the relationship between rights and obligations of the insured individuals and beneficiaries in the social assistance scheme. Those are values of liberty and equality, property, and community membership that can determine the boundaries of solidarity.
Keywords: communitarianism; komunitarizem; liberalism; liberalizem; libertarianism; libertarizem; social assistance; social insurance; social rights; socialne pravice; socialno varstvo; socialno zavarovanje